La mejora de la eficacia de la cooperación mediante la mejora en la utilización de los instrumentos de planificación. El caso de la OTC de República Dominicana - Encinas, Miguel Ángel; Sayos del Castillo, Vanessa (Revista Española de Desarrollo y Cooperación, 2023)
The article presents the work of the Spanish Technical Office for Cooperation in Dominican Republic and its aim to improve the quality of its management work, the planning of their interventions and more concretely, an iniciative experience that permitted, for the first time and by hazard, to combine theory and reality establishing a so called «operative framework for field interventions» under the strategic lines of the Spanish Agency for International Cooperation.